2020
DOI: 10.4013/sdrj.2020.133.06
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of design for social innovation and design activism in the promotion of positive social capital during the COVID-19 pandemic in Brazil.

Abstract: This case study aimed at mapping initiatives of social innovation that have promoted positive social capital during the COVID-19 pandemic in Brazil. To this end, information about the actions and their developers were collected online and further described using the forms "Light Format" and "In-Depth Format", from the toolkit developed by the Design for Social Innovation and Sustainability (DESIS) Network. In addition, interviews with the people involved in the projects were carried out in order to obtain furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Andion (2020), Igwe et al (2020), andPrado et al (2020) focussed on collective actions to respond to the needs caused by the pandemic (e.g., fundraising for the distribution of food or the purchase of protective and hospital equipment, information sharing). Using semi-structured interviews, Igwe et al (2020) documented the formation of solidarity networks in times of crisis in Nigeria.…”
Section: Results On Topicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Andion (2020), Igwe et al (2020), andPrado et al (2020) focussed on collective actions to respond to the needs caused by the pandemic (e.g., fundraising for the distribution of food or the purchase of protective and hospital equipment, information sharing). Using semi-structured interviews, Igwe et al (2020) documented the formation of solidarity networks in times of crisis in Nigeria.…”
Section: Results On Topicsmentioning
confidence: 99%
“…Andion (2020) performed an analysis of the actors of solidarity in Brazil based on existing datasets and showed that times of crisis have elements of continuity with the past activism scene, but crises also provide an important space for a "reinvention of civil society" and for the emergence of social experimentations and innovations: Indeed, she found that while many of the actors of these campaigns were already protagonists on the activism scene, also new actors emerged, namely the peripheral communities that in certain occasions had a leading role. Prado et al (2020), who conducted their study in Brazil as well, used a mixed-method approach and found that the initiatives that emerged were very heterogeneous, as they had different targets (e.g., ordinary consumers vs. vulnerable people); also in this case they could show how the pandemic situation brought to innovations in daily tasks (for instance the creation online platforms to buy necessary products or to disseminate information). Margolies and Strub (2021) examined a peculiar Mexican regional music response to the COVID-19 pandemic in the música huasteca community (música huasteca is a traditional Mexican musical style).…”
Section: Results On Topicsmentioning
confidence: 99%
See 3 more Smart Citations